PELATIHAN GOAL SETTING “GOAL GETTER” UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Ema Zati baroroh; Kiki amalia; Mia Asri Azzahra; Santi Ramadhani Putri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Low learning motivation is a common challenge for students, especially those with busy schedules at school and in Islamic boarding schools (pesantren). This study aims to test the effectiveness of the